Prognostic Impact of miR-224 and RAS Mutations in Medullary Thyroid Carcinoma. (6th June 2017) - Cavedon, Elisabetta; Barollo, Susi; Bertazza, Loris; Pennelli, Gianmaria; Galuppini, Francesca; Watutantrige-Fernando, Sara; Censi, Simona; Iacobone, Maurizio; Benna, Clara; Vianello, Federica; Zovato, Stefania; Nacamulli, Davide; et al.
Abstract : Little is known about the function of microRNA-224 (miR-224) in medullary thyroid cancer (MTC). This study investigated the role of miR-224 expression in MTC and correlated it with mutation status in sporadic MTCs. A consecutive series of 134 MTCs were considered. Patients had a sporadic form in 80% of cases (107/134). In this group, REarranged during transfection ( RET ) and rat sarcoma ( RAS ) mutation status were assessed by direct sequencing in the tumor tissues. Quantitative real-time polymerase chain reaction was used to quantify mature hsa-miR-224 in tumor tissue. RAS (10/107 cases, 9%) and RET (39/107 cases, 36%) mutations were mutually exclusive in sporadic cases. miR-224 expression was significantly downregulated in patients with the following: high calcitonin levels at diagnosis (p = 0.03, r = − 0.3 ); advanced stage (p = 0.001 ); persistent disease (p = 0.001 ); progressive disease (p = 0.002 ); and disease-related death (p = 0.0001 ). We found a significant positive correlation between miR-224 expression and somatic RAS mutations (p = 0.007 ). Patients whose MTCs had a low miR-224 expression tended to have a shorter overall survival (log-rank test p = 0.005 ). On multivariate analysis, miR-224 represented an independent prognostic marker. Our data indicate that miR-224 is upregulated in RAS -mutated MTCs and in patients with a better prognosis and could represent an independent prognostic marker in MTC patients.